ZnSnO3 / ZnO nanocomposite materials and their application in formaldehyde detection

Through the application of ZNSNO3/ZNO nano composite material, the problem of high working temperature and low response value at the high -working and low -response value of formaldehyde at low temperatures is detected by the existing formaldehyde gas sensor at low temperature. Essence

CN116891250BActive Publication Date: 2025-01-28ANHUI UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310831657.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-07
Publication Date
2025-01-28
Estimated Expiration
2043-07-07

AI Technical Summary

Technical Problem

The existing formaldehyde gas sensors based on MOS have problems such as high operating temperature, high energy consumption, low response value and long recovery time, and it is difficult to effectively detect formaldehyde in complex atmospheres.

Method used

The Znsno3/Zno nano composite material is used to prepare a gas sensor with high sensitivity, selectivity, and short response time by mixed Znsno3 nano -material with Zno quantum dot.

Benefits of technology

The detection of high sensitivity, selectivity, and short response/recovery time of formaldehyde at a low temperature of 70 ° C is suitable for the development of portable gas sensors. It can highly detect formaldehyde in the complex gas atmosphere.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116891250B_ABST
    Figure CN116891250B_ABST
Patent Text Reader

Abstract

The invention discloses a ZnSnO3 / ZnO nanocomposite material and its application in formaldehyde detection. The invention uses zinc acetate dihydrate as a raw material and combines a sol-gel method and a precipitation method to obtain ZnO quantum dots, and then uses zinc acetate dihydrate, tin chloride pentahydrate, potassium hydroxide and sodium fluoride to hydrothermally react and calcine to obtain ZnSnO3 nanopowder, and the ZnO quantum dots are doped and composited to obtain a ZnSnO3 / ZnO nanocomposite material. The ZnSnO3 / ZnO nanocomposite material is made into a gas sensor, and its gas-sensitive performance to formaldehyde gas is detected after high-temperature aging. The invention provides a method for preparing a ZnSnO3 / ZnO nanocomposite material sensor with low preparation cost and simple method. The gas sensor has high sensitivity, selectivity and short response and recovery time to formaldehyde at a low temperature of 70°C, and provides a feasible solution for the development of portable gas sensors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of gas-sensitive sensing materials, and in particular relates to a ZnSnO3 / ZnO nanocomposite gas-sensitive material and its application in gas detection sensors. Background Art

[0002] Formaldehyde is an important industrial raw material used in various industries, such as flooring, coatings, composite materials, composite adhesives, disinfectants, food preservatives, etc. However, the toxicity of formaldehyde is recognized. It reacts with human DNA, proteins, etc., and long-term contact can lead to cancer. Due to the application of formaldehyde in the production and preparation of various indoor decoration materials, formaldehyde has also become one of the most common pollutants in the indoor environment, and it has a long release time and a high cure rate. People spend 60%-90% of their time working and living indoors. Therefore, it is stipulated that the indoor formaldehyde concentration is controlled within 0.10 mg per cubic meter (0.07ppm). Therefore, the development of a high-performance formaldehyde sensor is of great significance for the detection of formaldehyde in indoor environments.

[0003] Compared with traditional spectroscopy or chromatography methods that rely on large equipment and technology, semiconductor metal oxide (MOS) gas sensors have attracted much attention and have attracted extensive research due to their simple manufacturing methods, small and portable size, easy operation, low cost, rapid response and real-time detection. For example, Ge W et al. prepared a porous In2O3-SnO2 hybrid porous nanostructure for formaldehyde detection. Studies have shown that compared with pure SnO2, the hybrid nanostructure containing 3% In2O3 has a maximum response value of 30.7 to 100 ppm of formaldehyde at 100°C, which is 14 times that of the original. Despite this, there are still many problems with current MOS-based formaldehyde gas sensors, such as reliance on high operating temperatures, high energy consumption, low response values ​​and long recovery time, and they cannot effectively detect formaldehyde in complex atmospheres.

[0004] Perovskite ABO3 (A is a rare metal, B is a transition metal ion) is a new material with special structural properties discovered in recent years. Among them, zinc stannate (ZnSnO3) is a typical rare earth composite metal oxide with a perovskite (ABO3) structure. Due to its various super performance characteristics such as stable crystal structure, non-toxicity and small band gap energy, ZnSnO3 has a wide range of application prospects in the fields of optics, catalysis and sensors, and has become a hot topic of research at home and abroad. At present, ZnSnO3 has become one of the most promising materials for the preparation of new nano-composite metal oxide semiconductor sensors. Previous studies have shown that pure ZnSnO3 has a certain selectivity for formaldehyde, but the working temperature is high and the response value cannot meet the application requirements. Summary of the invention

[0005] In view of the above technical problems encountered in the prior art, the present invention proposes a simple new gas sensing material that can increase the gas-sensitive response of ZnSnO3 to formaldehyde and reduce its working temperature. By obtaining a gas sensor with high sensitivity, selectivity and short response (response time 1-3 seconds) and recovery time (recovery time about 300 seconds) to formaldehyde at a low temperature of 70°C, and based on this, a portable gas sensor can be developed to effectively detect formaldehyde safely and efficiently in a complex gas atmosphere. Specifically, the present invention is implemented by the following technical solutions:

[0006] The ZnSnO3 / ZnO nanocomposite material of the present invention is obtained by mixing, drying and grinding ZnSnO3 nanomaterial and ZnO quantum dots, wherein the ZnO quantum dots account for 1wt%-20wt%, preferably 2wt%-10wt%, more preferably 3wt%-6wt%, and most preferably 5wt%.

[0007] The ZnSnO3 / ZnO nanocomposite material of the present invention is obtained by keeping ZnSnO3 precursor powder in air at 400-500°C for 1-3 hours; the ZnSnO3 precursor powder is obtained by hydrothermally reacting zinc acetate dihydrate, tin chloride pentahydrate, potassium hydroxide and sodium fluoride in a polytetrafluoroethylene reactor at 130-160°C for 10-15 hours. It is better to keep the ZnSnO3 precursor powder in air at 450°C for 2 hours; preferably, the reaction materials are 1mmol of zinc acetate dihydrate, 1mmol of tin chloride pentahydrate, 10mmol of potassium hydroxide and 0.1g of sodium fluoride; and it is better to react the hydrothermally at 140°C for 12 hours.

[0008] The ZnSnO3 / ZnO nanocomposite material of the present invention, wherein the ZnO quantum dots are obtained by adding a lithium hydroxide solution dropwise into an ethanol solution of zinc acetate dihydrate, stirring at room temperature and pressure, and then adding ethyl acetate for precipitation.

[0009] As a preferred solution, the ZnSnO3 / ZnO nanocomposite material of the present invention is obtained by the following preparation method:

[0010] (1) adding a lithium hydroxide ethanol solution dropwise to a zinc acetate dihydrate ethanol solution, stirring at room temperature and pressure for one hour, adding an excess of ethyl acetate solution until the ZnO quantum dots are completely precipitated, taking out the product, washing, centrifuging and drying at 70-90° C. for 20-30 hours to obtain ZnO quantum dots; the molar ratio of zinc acetate dihydrate: lithium hydroxide is 1:2; this step is carried out at room temperature and pressure to prepare ZnO quantum dots. The higher the temperature, the more severe the quantum dots agglomerate. The quantum dots prepared at room temperature will not agglomerate and the preparation conditions are simple; ethyl acetate is a common precipitant used to precipitate quantum dots;

[0011] (2) Dissolve zinc acetate dihydrate, tin chloride pentahydrate, potassium hydroxide and sodium fluoride in distilled water, stir evenly, transfer to a 100 mL polytetrafluoroethylene reactor, react at 130-150° C. for 10-15 hours, take out the product, wash and centrifuge, and dry at 70-90° C. for 20-30 hours. Grind the completely dried product into powder to obtain ZnSnO3 precursor powder ZnSn(OH)6;

[0012] (3) The ZnSnO3 precursor powder is placed in a muffle furnace, heated to 400-500°C in air at a heating rate of 1-3°C / min, kept at this temperature for 1-3 hours, and then naturally cooled to room temperature to take out the target product, thereby obtaining ZnSnO3 nanomaterials.

[0013] (4) Add the above ZnSnO3 nanomaterial to an ethanol solution, then add ZnO quantum dots, stir and ultrasonicate until completely mixed, dry at 70-90°C for 20-30 hours, grind the completely dried product into powder, and obtain a ZnSnO3 / ZnO composite nanomaterial. The mass percentage of ZnO quantum dots can be 1wt%-20wt%, preferably 2wt%-10wt%, more preferably 3wt%-6wt%, and most preferably 5wt%, based on the total mass of the ZnSnO3 nanomaterial and the ZnO quantum dots.

[0014] The ZnSnO3 / ZnO nanocomposite material of the present invention can be used as a gas-sensitive material in the detection of gases such as formaldehyde. In the application, the composite material can be made into a gas-sensitive element or a gas-sensitive sensor; specifically, in the application, the composite material can be made into a slurry by adding some solvents such as pine oil alcohol, etc., and coated on an alumina ceramic tube, and then welded to a ceramic base after drying and equipped with a resistance wire to make a gas-sensitive element, and the gas-sensitive element is heated to 200-300°C and aged for 5-8 hours, preferably 250°C for 6 hours to obtain a gas-sensitive sensor.

[0015] The invention uses zinc acetate dihydrate as a raw material and combines a sol-gel method and a precipitation method to obtain ZnO quantum dots. Then, a precursor obtained by a hydrothermal reaction of zinc acetate dihydrate, tin chloride pentahydrate, potassium hydroxide and sodium fluoride is calcined in air to obtain ZnSnO3 nanopowder, which is doped and composited with the ZnO quantum dots prepared in the early stage to obtain a ZnSnO3 / ZnO nanopowder material. The synthesized gas-sensitive material is coated on an alumina ceramic tube loaded with a platinum electrode with pine oil to prepare a gas sensor, and its gas-sensitive performance to formaldehyde gas is detected after high-temperature aging. The invention adopts a physical dispersion mixing method to obtain a ZnSnO3 / ZnO composite material, and the preparation process is relatively simple. It is a preparation scheme for gas-sensitive materials with low equipment investment and simple process flow. The ZnO prepared by the sol-gel method in the invention is nanometer-level, the agglomeration of ZnO quantum dots is reduced at room temperature and pressure, LiOH increases the concentration of surface negative charges, greatly increases the effect of electrostatic repulsion between quantum dots, and better controls the particle size of ZnO.

[0016] The ZnSnO3 / ZnO composite material of the present invention is a porous hierarchical structure. The ZnSnO3 nanomaterial prepared by the hydrothermal method has good chemical uniformity and fine particles. Annealing and sintering cause a large number of lattice defects to appear inside it. The physical mixing method is simple, and the ultra-microstructures such as particle size and uniformity of different doping contents are effectively controlled, providing more active sites, promoting additional chemical oxygen adsorption on the surface of the material, and effectively promoting charge transfer, thereby improving the gas-sensitive performance of the material. The composite material of the present invention has the advantages of large specific surface area, high sensitivity to low-concentration formaldehyde gas, good selectivity, and short response / recovery time. With the increase of the doping amount of ZnO quantum dots, it shows high selectivity and high response to formaldehyde gas; at the same time, the composite material can show better detection response to formaldehyde gas at an operating temperature of 70-120°C; especially when the doping amount is 5wt% and the operating temperature is 70°C, the ZSO / ZO-0.05 composite material has the best formaldehyde response value, thereby realizing low-temperature, portable and efficient detection of formaldehyde gas, and providing a feasible solution for the development of portable gas sensors. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 The crystal X-ray diffraction patterns of ZnSnO3 / ZnO composite nanomaterials doped with ZnO quantum dots in different proportions prepared in Examples 1-5 of the present invention.

[0018] Figure 2 This is a scanning electron microscope image of the ZnSnO3 / ZnO (ie, ZSO / ZO-0.05) composite nanomaterial doped with 5 wt% ZnO quantum dots prepared in Example 3 of the present invention.

[0019] Figure 3Example 1: Prepare pure ZnSnO3 material sensor to respond to different gases with a concentration of 100 ppm at different temperatures.

[0020] Figure 4 Example 2: Prepare the response diagrams of ZSO / ZO-0.01 (i.e. ZnSnO3 / ZnO doped with 1 wt% ZnO quantum dots) composite material sensor to different gases with a concentration of 100 ppm at different temperatures.

[0021] Figure 5 Example 3: Prepared ZSO / ZO-0.05 composite material sensor to respond to different gases with a concentration of 100 ppm at different temperatures.

[0022] Figure 6 Example 4: Prepared ZSO / ZO-0.10 composite material sensor to respond to different gases at a concentration of 100 ppm at different temperatures.

[0023] Figure 7 Example 5: Preparation of ZSO / ZO-0.20 composite material sensor responses to different gases at a concentration of 100 ppm at different temperatures.

[0024] Figure 8 Comparison of the responses of the ZnSnO3 and different ZSO / ZO composite materials sensors prepared in Examples 1-5 to formaldehyde at a concentration of 100 ppm at different temperatures.

[0025] Fig. 9 The gas-sensitive response diagram of the ZSO / ZO-0.05 composite material sensor prepared in Example 3 of the present invention at 70°C is as follows: a) a resistance response change curve to 0.3-100ppm acetone gas; b) a relationship diagram between the gas-sensitive response value and the concentration. DETAILED DESCRIPTION

[0026] The following embodiments are further descriptions of the content of the present invention as an explanation of the technical content of the present invention, but the essential content of the present invention is not limited to the following embodiments. Ordinary technicians in this field can and should know that any simple changes or replacements based on the essential spirit of the present invention should fall within the scope of protection required by the present invention.

[0027] Embodiment 1:

[0028] The preparation method of pure ZnSnO3 nanomaterial (without adding ZnO quantum dots) gas sensor includes the following steps:

[0029] (1) Zinc acetate dihydrate, tin chloride pentahydrate, potassium hydroxide and sodium fluoride (1 mmol of zinc acetate dihydrate, 1 mmol of tin chloride pentahydrate, 10 mmol of potassium hydroxide and 0.1 g of sodium fluoride) were dissolved in 80 mL of distilled water, stirred evenly, and transferred to a 100 mL polytetrafluoroethylene reactor. The mixture was reacted at 140° C. for 12 hours. The product was taken out, washed, centrifuged and dried at 80° C. for 24 hours. The completely dried product was ground into powder to obtain ZnSnO3 precursor ZnSn(OH)6 powder.

[0030] (2) The ZnSnO3 precursor powder is placed in a muffle furnace, heated to 450°C in air at a heating rate of 2°C / min, kept at this temperature for 2 hours, and then naturally cooled to room temperature to take out the target product, thereby obtaining ZnSnO3 nanomaterials.

[0031] (3) The above ZnSnO3 nanomaterial is added to an ethanol solution without adding ZnO quantum dots, stirred and ultrasonicated until completely mixed, dried at 80°C for 24 hours, and the completely dried product is ground into powder to obtain pure ZnSnO3 nanomaterial.

[0032] (4) Take 15 mg of the above product and put it into an agate mortar, grind it for 5-10 minutes, add an appropriate amount of pine alcohol and continue grinding for 5-10 minutes until it is fully mixed, and evenly coat it on an alumina ceramic tube and dry it at 80°C for 24 hours. The obtained ceramic tube is welded to a ceramic base and equipped with a resistance wire (to provide reaction temperature) to make a gas sensor. The gas sensor is heated to 250°C and aged for 6 hours to obtain a stable gas sensor.

[0033] (5) Test the gas sensing performance of gas sensors to different gases at different temperatures.

[0034] Embodiment 2:

[0035] The preparation method of the gas sensor based on the ZnSnO3 / ZnO-0.01 nanocomposite material includes the following steps:

[0036] (1) Zinc acetate dihydrate is dissolved in an anhydrous ethanol solvent solution, and lithium hydroxide solution is added dropwise to the solution (zinc acetate dihydrate: lithium hydroxide = 1:2), and stirred at room temperature and pressure for one hour, and an excess of ethyl acetate solution is added until the ZnO quantum dots are completely precipitated. The product is taken out, washed, centrifuged and dried at 80°C for 24 hours to obtain ZnO quantum dots.

[0037] (2) Zinc acetate dihydrate, tin chloride pentahydrate, potassium hydroxide and sodium fluoride are dissolved in 80 mL of distilled water (this step is the same as the step in Example 1 (1)), stirred evenly, transferred to a 100 mL polytetrafluoroethylene reactor, reacted at 140° C. for 12 hours, the product was taken out, washed, centrifuged and dried at 80° C. for 24 hours, and the completely dried product was ground into powder to obtain ZnSnO3 precursor ZnSn(OH)6 powder.

[0038] (3) The ZnSnO3 precursor powder is placed in a muffle furnace, heated to 450°C in air at a heating rate of 2°C / min, kept at this temperature for 2 hours, and then naturally cooled to room temperature to take out the target product, thereby obtaining ZnSnO3 nanomaterials.

[0039] (4) The above ZnSnO3 nanomaterial was added to an ethanol solution, and a certain amount of ZnO quantum dots (mass percentage of 1 wt%) were added respectively, and the mixture was stirred and ultrasonicated until completely mixed, and dried at 80°C for 24 hours. The completely dried product was ground into powder to obtain a ZnSnO3 / ZnO composite nanomaterial (denoted as ZSO / ZO-0.01).

[0040] (5) Take 15 mg of the above product and put it into an agate mortar, grind it for 5-10 minutes, add an appropriate amount of pine alcohol and continue grinding for 5-10 minutes until it is fully mixed, and evenly coat it on an alumina ceramic tube, and dry it at 80°C for 24 hours. The obtained ceramic tube is welded to a ceramic base and equipped with a resistance wire (to provide reaction temperature) to make a gas sensor. The gas sensor is heated to 250°C and aged for 6 hours to obtain a stable gas sensor.

[0041] (6) The performance of the gas sensor was tested. The resistance response of the device to 100 ppm formaldehyde was 466 times that in air, and the optimal operating temperature was 70°C.

[0042] Embodiment 3:

[0043] The preparation method of the gas sensor based on the ZnSnO3 / ZnO-0.05 nanocomposite material includes the following steps:

[0044] (1) Zinc acetate dihydrate is dissolved in an anhydrous ethanol solvent solution, lithium hydroxide solution is added dropwise to the solution (this step is the same as the step of Example 2 (1)), and stirred at room temperature and pressure for one hour, and an excess of ethyl acetate solution is added until the ZnO quantum dots are completely precipitated. The product is taken out, washed, centrifuged and dried at 80° C. for 24 hours to obtain ZnO quantum dots.

[0045] (2) Zinc acetate dihydrate, tin chloride pentahydrate, potassium hydroxide and sodium fluoride are dissolved in 80 mL of distilled water (this step is the same as the step in Example 1 (1)), stirred evenly, transferred to a 100 mL polytetrafluoroethylene reactor, reacted at 140° C. for 12 hours, the product was taken out, washed, centrifuged and dried at 80° C. for 24 hours, and the completely dried product was ground into powder to obtain ZnSnO3 precursor ZnSn(OH)6 powder.

[0046] (3) The ZnSnO3 precursor powder is placed in a muffle furnace, heated to 450°C in air at a heating rate of 2°C / min, kept at this temperature for 2 hours, and then naturally cooled to room temperature to take out the target product, thereby obtaining ZnSnO3 nanomaterials.

[0047] (4) The above ZnSnO3 nanomaterials were added to an ethanol solution, and a certain amount of ZnO quantum dots (mass percentage of 5 wt%) were added respectively, and the mixture was stirred and ultrasonicated until completely mixed, and dried at 80°C for 24 hours. The completely dried product was ground into powder to obtain a ZnSnO3 / ZnO composite graded nanomaterial (denoted as ZSO / ZO-0.05).

[0048] (5) Take 15 mg of the above product and put it into an agate mortar, grind it for 5-10 minutes, add an appropriate amount of pine alcohol and continue grinding for 5-10 minutes until it is fully mixed, and evenly coat it on an alumina ceramic tube, and dry it at 80°C for 24 hours. The obtained ceramic tube is welded to a ceramic base and equipped with a resistance wire (to provide reaction temperature) to make a gas sensor. The gas sensor is heated to 250°C and aged for 6 hours to obtain a stable gas sensor.

[0049] (6) The performance of the gas sensor was tested. The resistance response of the device to 100 ppm formaldehyde was 613 times that in air, and the optimal operating temperature was 70°C.

[0050] Embodiment 4:

[0051] The preparation method of the gas sensor based on the ZnSnO3 / ZnO-0.10 nanocomposite material includes the following steps:

[0052] (1) Zinc acetate dihydrate is dissolved in anhydrous ethanol solvent solution, lithium hydroxide solution is added dropwise to the solution (this step is the same as the step of Example 2 (1)), and stirred at room temperature and pressure for one hour, and an excess of ethyl acetate solution is added until the ZnO quantum dots are completely precipitated. The product is taken out, washed, centrifuged and dried at 80°C for 24 hours to obtain ZnO quantum dots.

[0053] (2) Zinc acetate dihydrate, tin chloride pentahydrate, potassium hydroxide and sodium fluoride are dissolved in 80 mL of distilled water (this step is the same as the step in Example 1 (1)), stirred evenly, transferred to a 100 mL polytetrafluoroethylene reactor, reacted at 140° C. for 12 hours, the product was taken out, washed, centrifuged and dried at 80° C. for 24 hours, and the completely dried product was ground into powder to obtain ZnSnO3 precursor ZnSn(OH)6 powder.

[0054] (3) The ZnSnO3 precursor powder is placed in a muffle furnace, heated to 450°C in air at a heating rate of 2°C / min, kept at this temperature for 2 hours, and then naturally cooled to room temperature to take out the target product, thereby obtaining ZnSnO3 nanomaterials.

[0055] (4) The above ZnSnO3 nanomaterial was added to an ethanol solution, and a certain amount of ZnO quantum dots (mass percentage of 10wt%) were added respectively, stirred and ultrasonicated until completely mixed, and dried at 80°C for 24 hours. The completely dried product was ground into powder to obtain a ZnSnO3 / ZnO composite nanomaterial (denoted as ZSO / ZO-0.10).

[0056] (5) Take 15 mg of the above product and put it into an agate mortar, grind it for 5-10 minutes, add an appropriate amount of pine alcohol and continue grinding for 5-10 minutes until it is fully mixed, and evenly coat it on an alumina ceramic tube, and dry it at 80°C for 24 hours. The obtained ceramic tube is welded to a ceramic base and equipped with a resistance wire (to provide reaction temperature) to make a gas sensor. The gas sensor is heated to 250°C and aged for 6 hours to obtain a stable gas sensor.

[0057] (6) The performance of the gas sensor was tested. The resistance response of the device to 100 ppm formaldehyde was 417 times that in air, and the optimal operating temperature was 70°C.

[0058] Embodiment 5:

[0059] The preparation method of the gas sensor based on the ZnSnO3 / ZnO-0.20 nanocomposite material includes the following steps:

[0060] (1) Zinc acetate dihydrate is dissolved in an anhydrous ethanol solvent solution, lithium hydroxide solution is added dropwise to the solution (this step is the same as the step of Example 2 (1)), and stirred at room temperature and pressure for one hour, and an excess of ethyl acetate solution is added until the ZnO quantum dots are completely precipitated. The product is taken out, washed, centrifuged and dried at 80° C. for 24 hours to obtain ZnO quantum dots.

[0061] (2) Zinc acetate dihydrate, tin chloride pentahydrate, potassium hydroxide and sodium fluoride are dissolved in 80 mL of distilled water (this step is the same as the step in Example 1 (1)), stirred evenly, transferred to a 100 mL polytetrafluoroethylene reactor, reacted at 140° C. for 12 hours, the product was taken out, washed, centrifuged and dried at 80° C. for 24 hours, and the completely dried product was ground into powder to obtain ZnSnO3 precursor ZnSn(OH)6 powder.

[0062] (3) The ZnSnO3 precursor powder is placed in a muffle furnace, heated to 450°C in air at a heating rate of 2°C / min, kept at this temperature for 2 hours, and then naturally cooled to room temperature to take out the target product, thereby obtaining ZnSnO3 nanomaterials.

[0063] (4) The above ZnSnO3 nanomaterial was added to an ethanol solution, and a certain amount of ZnO quantum dots (mass percentage of 20wt%) were added respectively, and the mixture was stirred and ultrasonicated until completely mixed, and dried at 80°C for 24 hours. The completely dried product was ground into powder to obtain a ZnSnO3 / ZnO nanocomposite material (denoted as ZSO / ZO-0.20).

[0064] (5) Take 15 mg of the above product and put it into an agate mortar, grind it for 5-10 minutes, add an appropriate amount of pine alcohol and continue grinding for 5-10 minutes until it is fully mixed, and evenly coat it on an alumina ceramic tube, and dry it at 80°C for 24 hours. The obtained ceramic tube is welded to a ceramic base and equipped with a resistance wire (to provide reaction temperature) to make a gas sensor. The gas sensor is heated to 250°C and aged for 6 hours to obtain a stable gas sensor.

[0065] (6) The performance of the gas sensor was tested. The resistance response of the device to 100 ppm formaldehyde was 309.4 times that in air, and the optimal operating temperature was 70°C.

[0066] Figure 1 The crystal X-ray diffraction patterns of ZnSnO3 / ZnO nanocomposites doped with different proportions of ZnO quantum dots prepared in Examples 1 to 5 of the present invention are shown in Table 1. It can be found that ZnSnO3 is an amorphous structure, and ZnO quantum dots have diffraction peaks as the doping amount increases. The results show that the ZnSnO3 / ZnO composite material was successfully synthesized.

[0067] Figure 2 This is a scanning electron microscope image of a ZnSnO3 / ZnO (ZSO / ZO-0.05) nanocomposite material doped with 5 wt% ZnO quantum dots prepared in Example 3 of the present invention. The composite material is composed of cubic blocks with a size of 100-200 nanometers.

[0068] Figure 3Example 1 Prepare pure ZnSnO3 material sensor to respond to different gases at 100ppm concentration at different temperatures. The results show that the pure ZnSnO3 material sensor has a certain response to various gases, reaching the maximum at 170℃ for formaldehyde, and can only reach 32 for 100ppm formaldehyde, while the response to formic acid gas is also close to 20, and it lacks response to certain gases.

[0069] Figure 4 Example 2 Prepare the ZSO / ZO-0.01 nanocomposite sensor to different gas responses at 100ppm concentration at different temperatures. The results show that compared with other gases, the ZSO / ZO-0.01 composite material only has a significant response to formaldehyde, and reaches a maximum at 70°C, reaching 450 for 100ppm formaldehyde, and the response value decreases with increasing temperature, indicating that 70°C is its optimal operating temperature.

[0070] Figure 5 Example 3 Prepare the ZSO / ZO-0.05 nanocomposite sensor to respond to different gases at 100ppm concentration at different temperatures. The results show that compared with other gases, the ZSO / ZO-0.05 composite material only has a significant response to formaldehyde, and reaches the maximum at 70℃, and the response to 100ppm formaldehyde reaches 600. As the temperature increases, the response value decreases. Indicates that its optimal working temperature is 70℃.

[0071] Figure 6 Example 4 Prepared ZSO / ZO-0.10 nanocomposite sensor to respond to different gases at 100ppm concentration at different temperatures. The results show that compared with other gases, ZSO / ZO-0.10 composite material only has a significant response to formaldehyde, and reaches the maximum at 70℃, and the response to 100ppm formaldehyde reaches 400. As the temperature increases, the response value decreases. This shows that its optimal working temperature is 70℃

[0072] Figure 7 Example 5 Preparation of ZSO / ZO-0.20 nanocomposite sensor to different gas responses at 100ppm concentration at different temperatures. The results show that compared with other gases, ZSO / ZO-0.20 composite material only has a significant response to formaldehyde, and reaches the maximum at 70℃, and the response to 100ppm formaldehyde reaches 350, and the response value decreases with the increase of temperature. It shows that its optimal working temperature is 70℃.

[0073] Figure 8The responses of ZnSnO3 and different ZSO / ZO nanocomposite sensors prepared in Examples 1-5 to formaldehyde at a concentration of 100ppm at different temperatures were compared. The results showed that the ZnSnO3 gas sensor without ZnO quantum dots had no high response to formaldehyde, but with the doping of ZnO quantum dots, it showed high selectivity and high response to formaldehyde gas, and when the doping amount was 5wt%, the response value of ZSO / ZO-0.05 composite material to formaldehyde reached the maximum, and the optimal working temperature was 70°C.

[0074] Fig. 9 The gas-sensitive response diagram of the ZSO / ZO-0.05 nanocomposite sensor prepared in Example 3 of the present invention at 70°C is shown as a) a resistance response change curve to 0.3-100ppm formaldehyde gas; b) a relationship diagram between the gas-sensitive response value and the concentration. It can be seen from the figure that with the increase of formaldehyde concentration, the response value of the gas sensor increases, and it can be completely and quickly recovered within a test cycle, indicating that it has good cycle performance and stable performance. From the linear relationship diagram between its response and concentration, it can also be seen that the high response of the gas sensor to formaldehyde is conducive to its highly selective detection of formaldehyde in a complex gas atmosphere.

[0075] It should be noted that the above-mentioned technical contents of the present invention are only for explanation and clarification to enable those skilled in the art to understand the technical essence of the present invention, so the technical contents are not used to limit the substantial protection scope of the present invention. The substantial protection scope of the present invention shall be subject to the claims. Those skilled in the art should know that any modification, equivalent substitution and improvement based on the substantial spirit of the present invention shall be within the substantial protection scope of the present invention.

Claims

1. ZnSnO3 / ZnO nanocomposite material, which is obtained by mixing, drying and grinding ZnSnO3 nanomaterial and ZnO quantum dots, wherein: The ZnO quantum dots account for 3wt%-6wt%; the mixing is to add ZnSnO3 nanomaterials into an ethanol solution, then add ZnO quantum dots, and stir and mix with ultrasound; The ZnSnO3 nanomaterial is obtained by keeping the ZnSnO3 precursor powder in air at 400-500°C for 1-3 hours; the ZnSnO3 precursor powder is obtained by hydrothermally reacting 1 mmol of zinc acetate dihydrate, 1 mmol of tin chloride pentahydrate, 10 mmol of potassium hydroxide and 0.1 g of sodium fluoride in a polytetrafluoroethylene reactor at 130-160°C for 10-15 hours; The ZnO quantum dots are obtained by adding a lithium hydroxide solution dropwise into an ethanol solution of zinc acetate dihydrate, stirring at room temperature and pressure, and then adding ethyl acetate for precipitation; The ZnSnO3 / ZnO nanocomposite material is obtained by the following preparation method: (1) adding an ethanol solution of lithium hydroxide dropwise to an ethanol solution of zinc acetate dihydrate, stirring at room temperature and pressure for one hour, adding an excess of ethyl acetate until the ZnO quantum dots are completely precipitated, taking out the product, washing, centrifuging and drying at 70-90° C. for 20-30 hours to obtain ZnO quantum dots; wherein the molar ratio of zinc acetate dihydrate to lithium hydroxide is 1:2; (2) Dissolve zinc acetate dihydrate, tin chloride pentahydrate, potassium hydroxide and sodium fluoride in distilled water, stir evenly, transfer to a polytetrafluoroethylene reactor, react at 130-150 °C for 10-15 hours, take out the product, wash and centrifuge, and dry at 70-90 °C for 20-30 hours. Grind the completely dried product into powder to obtain ZnSnO3 precursor powder ZnSn(OH)6; (3) placing the above ZnSnO3 precursor powder into a muffle furnace, heating it to 400-500°C in air at a heating rate of 1-3°C / min, keeping it at that temperature for 1-3 hours, then naturally cooling it to room temperature to take out the target product, and obtaining ZnSnO3 nanomaterials; (4) Add the above ZnSnO3 nanomaterial into an ethanol solution, then add ZnO quantum dots, stir and ultrasonicate until completely mixed, dry at 70-90°C for 20-30 hours, and grind the completely dried product into powder to obtain ZnSnO3 / ZnO composite nanomaterial.

2. The method for preparing the ZnSnO3 / ZnO nanocomposite material according to claim 1, characterized in that: The steps include: (1) adding lithium hydroxide ethanol solution dropwise to zinc acetate dihydrate ethanol solution, stirring at room temperature and pressure for one hour, adding excess ethyl acetate until ZnO quantum dots are completely precipitated, taking out the product, washing, centrifuging and drying at 70-90° C. for 20-30 hours to obtain ZnO quantum dots; the molar ratio of zinc acetate dihydrate to lithium hydroxide is 1:2; (2) Dissolve 1 mmol of zinc acetate dihydrate, 1 mmol of tin chloride pentahydrate, 10 mmol of potassium hydroxide and 0.1 g of sodium fluoride in distilled water, stir evenly, transfer to a polytetrafluoroethylene reactor, react at 130-150 °C for 10-15 hours, take out the product, wash and centrifuge it, and dry it at 70-90 °C for 20-30 hours. Grind the completely dried product into powder to obtain ZnSnO3 precursor powder ZnSn(OH)6; (3) placing the above ZnSnO3 precursor powder into a muffle furnace, heating it to 400-500°C in air at a heating rate of 1-3°C / min, keeping it at that temperature for 1-3 hours, then naturally cooling it to room temperature to take out the target product, and obtaining ZnSnO3 nanomaterials; (4) Add the above ZnSnO3 nanomaterial into an ethanol solution, then add ZnO quantum dots, stir and ultrasonicate until completely mixed, dry at 70-90°C for 20-30 hours, and grind the completely dried product into powder to obtain ZnSnO3 / ZnO composite nanomaterial.

3. Use of the composite material according to claim 1 as a gas-sensitive material in formaldehyde detection.

4. The use according to claim 3, characterized in that The composite material is made into a gas sensor.

5. The use according to claim 3, characterized in that The composite material is made into a gas sensor.

6. The use according to claim 3, characterized in that The composite material is made into slurry and coated on an alumina ceramic tube. After drying, the slurry is welded to a ceramic base and a resistance wire is added to make a gas sensitive element. The gas sensitive element is heated to 200-300° C. and aged for 5-8 hours to obtain a gas sensor.